Blue Economic Beacon: Red And White Leads The Way Through Niche Diplomacy - Pratiwi, Heni; Hutabarat, Zuhri Saputra; Nabila, Rahima; Hevinosa, Aqeela Dwi; Mauli, Cahaya; Syaputri, Ayang Heen; Nisa, Alkhoiriyatun; Hidayatullah, M. Syarif; Tyaningsih, Dwi Ramadhan; Putri, Devinda Inka; Fakhira, Afifa Lutfia; Aprilia, Mayang Dwi; Al Zahra, Fatimah (International Journal of Multidisciplinary Sciences and Arts, 2024)
This research has a specific objective to analyze the Indonesian government's strategy in realizing sustainable marine development based on its role as a middle power country. The author uses the theoretical framework of middle power identity and niche diplomacy to analyze the problems in this study. This research is a type of qualitative research that is explained using the explanatory method. Based on the results of the research, the Indonesian government's strategy is to prioritize sustainable marine development in national marine policy and also commit to contributing to the world's sustainable marine development with the blue economy principle. This commitment will be realized by increasing cooperation in the marine sector at the bilateral, multilateral and regional levels. Specifically, the form of the realization of this commitment is that Indonesia has become the strategy of the Indonesian government to realize sustainable marine development is to become the initiator of the formation of cooperation forums (coalition building), to become the contact person for countries in the interest of sustainable marine development (bridge builder), and to uphold international norms in the marine sector for the common good (catalyst).